Prediction of sound transmission loss of conical acoustic enclosure using statistical energy analysis and its experimental validation. (May 2023) - Gupta, Pavan; Parey, Anand
The conical shape structures are widely employed in many practical applications such as aircraft, rockets, tanks, and submarines. Prediction of sound transmission loss is often required at the design and evaluation stages of such structures. In this paper, an analytical model is proposed using the statistical energy analysis (SEA) technique to predict the sound transmission loss of a conical shape acoustic enclosure in a broad frequency range. The proposed model is verified experimentally using the sound intensity experimental technique. It was found that the analytical predictions are in good agreement with the measured transmission loss, specifically at the ring and critical frequencies. The percentage error between predicted and measured lower ring frequency is 5.1% and that for the upper ring frequency is 0.4%. The percentage error between predicted and measured critical frequency is 2.7%. The results obtained indicate that the developed analytical model can be used as an efficient design tool to predict the acoustic performance of conical shape structures.